Knowledge management in the Faculty of Economic Sciences – Regional Headquarters Itapua, Paraguay - Encina Fretes, Rosa E. (2021)
Fil: Encina Fretes, Rosa E. Universidad Católica "Nuestra Señora de la Asunción". Facultad de Ciencias Económicas; Paraguay.